A distribution-based selective optimization method for eliminating periodic defects in harmonic signals. (15th February 2023) - Xin, Qing-Yuan; Pei, Yong-Chen; Lu, Huiqi; Clifton, David; Wang, Bin; Qu, Chuan; Wang, Lu-Lu; Luo, Meng-Yan
Graphical abstract: Highlights: A selective optimization method is given to fit signals with large periodic defects. The proposed method can eliminate periodic defects and improve fitting accuracy. Effectiveness of the proposed selective optimization method is greater than 95%. Abstract: Due to environmental interference and defects in measured objects, measurement signals are frequently affected by unpredictable noise and periodic defects. Moreover, there is a lack of effective methods for accurately distinguishing defect components from measurement signals. In this study, a distribution-based selective optimisation method (SOM) is proposed to mitigate the effects of noise and defect components. The SOM can be seen as a binary- or multiple-class signal classifier based on an error distribution, which can simultaneously eliminate periodic defect components of measurement signals and proceed with signal-fitting regression. The effectiveness, accuracy, and feasibility of the SOM are verified in theoretical and realworld measurement settings. Based on theoretical simulations under various parameter conditions, some criteria for selecting operation variables among a selection of parameter conditions are explained in detail. The proposed method is capable of separating defect components from measurement signals while also achieving a satisfactory fitting curve for the measurement signals. The proposed SOM has broad application prospects in signal processing and defect detection for mechanical measurements, electronic filtering, instrumentation, part maintenance, and other fields.